An Optimal Design of Driving Mechanism in a 1 Degree of Freedom (d.o.f.) Anthropomorphic Finger - M. Ceccarelli; N. E. N. Rodríguez; G. Carbone; C. Lopez-Cajùn (Applied Bionics and Biomechanics)
Mechanisms can be used in finger design to obtain suitable actuation systems and to give stiff robust behavior in grasping tasks. The design of driving mechanisms for fingers has been attached at LARM in Cassino with the aim to obtain one degree of freedom actuation for an anthropomorphic finger. The dimensional design of a finger-driving mechanism has been formulated as a multi-objective optimization problem by using evaluation criteria for fundamental characteristics regarding with finger motion, grasping equilibrium and force transmission. The feasibility of the herein proposed optimum design procedure for a finger-driving mechanism has been tested by numerical examples that have been also used to enhance a prototype previously built at LARM in Cassino.